Internal Control System Of Merchant Inventory At Alfamart Basuki Rahmat Bengkulu - Riani, Gusti; Susanti, Neri; Astuty, Kamelia (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to find out: The Implementation of Internal Control applied by the company to Alfamart Stores. The Role of Internal Control on the Inventory of Merchandise in Alfamart Stores. The research method used is a comparative method with a descriptive approach. This research was conducted using interview and documentation techniques with parties involved in the Control of Alfamart Basuki Rahmat Bengkulu Merchandise Inventory. The results of the study show that the internal control system of merchandise inventory at Alfamart Basuki Rahmat Bengkulu is compatible with Mulyadi's theory (2018:488). In the organizational element, there is a schedule and committee involved in Stock Taking. The authorization system and recording procedures have been appropriate, where the monthly Stock Taking report is signed by the store head and the daily Stock Taking is signed by the shift holding employee, the recording after the results of the monthly and daily (partial) Stock Taking reports is calculated based on an invoice that contains the type of goods, the price of the goods and the quantity of goods. Sound practices, there is conformity in the implementation of the internal control system of merchandise inventory, where the invoice has been given a printed serial number and issued by WareHouse Alfamart, the implementation of Stock Taking is carried out 2 times (monthly and daily) using the PDA system.